Engleski - Cvetković, Vladimir M.; Čvorović, Milica; Beriša, Hatidza (NBP. Nauka, bezbednost, policija, 2023)
The subject of the research is an examination of the way in which the disease COVID-19 affects the gender aspects of the vulnerability of citizens, with special reference to their physical, socio-economic and psychological vulnerability. For the purposes of this research, the perception of risk and the preparedness of men and women for the SARS-CoV-2 virus pandemic was examined. The results of this research were obtained by applying a quantitative survey of the citizens of the Republic of Serbia about their experiences and attitudes regarding their vulnerability due to the COVID-19 pandemic, where special attention is paid to the gender dimension. A survey of 273 adult citizens was conducted and the results showed that there is no significant connection between the gender category and the physical vulnerability of people caused by the COVID-19 pandemic. The obtained data indicate that approximately the same percentage of women and men had severe symptoms of the disease. Nevertheless, the results showed that there is a partial connection between the gender category and socio-economic vulnerability, as well as a clear connection between the gender category and the psychological vulnerability of people caused by the pandemic. In both cases, the results indicate that women are more vulnerable socio-economically and psychologically than men. As this topic is not sufficiently represented in foreign, and especially not in domestic literature, the results of this research can serve as guidelines for future investigations of the gender dimension of people in the conditions of disasters, such as the COVID-19 pandemic.